Analisis Perawatan Berkala Trafo Distribusi 800 kVA pada Rumah Sakit X Kota Tangerang - Kusuma, Ridho Alpha; Prayogo, Jimmy Arimas; Mufit, Choirul (Elektrika, 2023)
In Indonesia, electricity supply for buildings or buildings with needs above 200kVA requires a distribution transformer owned by the customer, so that electrical energy transactions are carried out on the medium voltage side of 20kV. The distribution transformer in a hospital is a very vital component, especially during the COVID-19 pandemic where transformers are forced to continue operating above nominal levels without any maintenance. Distribution transformer maintenance includes visual inspection, monthly maintenance, maintenance every six months and annual maintenance. Treatments carried out on distribution transformers at X Hospital are DGA (Dissolved Gasses Analysis), transformer insulation testing, TTR (Transformer Turn Ratio) testing, Breakdown Voltage testing, thermovision testing and Winding Resistance testing; In addition, treatment or purification of transformer oil is also carried out based on testing. all dissolved gas and total dissolved gas (TDCG) decreased after the purification process and after purification there is still residual dissolved gas in the transformer. Interpretation of dissolved gas data (DGA) using several methods indicates a "Thermal Fault > 300 Celsius". This is in line with the results of thermovision on the transformer which shows a hot spot at the termination of the HV phase W bushing. Confirmation of this suspect will be checked after repairing the termination. Keywords: Distribution Transformer, Transformer, Maintenance. ABSTRAK Di Indonesia, suplai kelistrikan untuk bangunan atau gedung dengan kebutuhan diatas 200kVA maka diperlukan trafo distribusi yang dimiliki oleh pelanggan, sehingga transaksi energi listrik dilakukan di sisi tegangan menengah 20kV. Trafo distribusi di sebuah rumah sakit merupakan suatu komponen yang sangat vital, terutama selama masa pandemic COVID-19 dimana trafo dipaksa untuk tetap beroperasi diatas narus nominal tanpa adanya perawatan. Perawatan trafo distribusi meliputi inspeksi visual, perawatan bulanan, perawatan tiap enam bulan dan perawatan tahunan. Perawatan yang dilakukan di trafo distribusi di Rumah Sakit X ini adalah DGA (Dissolved Gasses Analysis), pengujian insulasi trafo, pengujian TTR (Transformer Turn Ratio), pengujian Breakdown Voltage, pengujian thermovision dan pengujian Winding Resistance, selain itu juga dilakukan treatment atau purifikasi oli trafo Berdasarkan pengujian. semua gas terlarut dan total gas terlarut (TDCG) menurun setelah proses pemurnian dan setelah pemurnian masih ada sisa gas terlarut di trafo. Interpretasi data gas terlarut (DGA) dengan beberapa metode menunjukkan adanya “Termal Fault > 300 Celcius”. Hal ini sejalan dengan hasil thermovision pada trafo yang menunjukkan adanya hot spot pada bagian terminasi busing W fasa HV. Konfirmasi tersangka ini akan dilakukan pengecekan setelah dilakukan perbaikan terminasi.